Paying for online news: a comparative analysis of six countries - Fletcher, R; Nielsen, R (Routledge, 2016)
Private news media across the world are trying to develop pay models for news. Our understanding of what drives behaviour and attitudes to paying for online news, however, remains limited. We use survey data from six countries (France, Germany, Japan, Spain, United Kingdom, and United States) to investigate three hypotheses: (1) those who use public service media for online news are less likely to pay for/express a willingness to pay because they have a reference price of zero for online news, (2) those who pay for print newspapers are more likely to pay for/express a willingness to pay for online news because they have a reference price above zero for offline news, and (3) that younger people are more likely to pay for/express a willingness to pay for online news because they are more likely to have a reference price above zero for other digital content. Our analysis supports Hypotheses 2 and 3, but not Hypothesis 1. Therefore, paying for offline news increases the likelihood of paying for online news because it helps create a reference price above zero. However, consuming free online news from public service media does not by itself create a reference price of zero for online news.